1974
DOI: 10.1073/pnas.71.12.4703
|View full text |Cite
|
Sign up to set email alerts
|

Type C Viral Antigens in Man. I. Antigens Related to Endogenous Primate Virus in Human Tumors

Abstract: Partially purified extracts from 33 human tumors of several histologic types were used as competing antigens irt a radioimmunoassay for the p30 protein of an endogenous primate type C virus (M7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1976
1976
1979
1979

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Various strains of type-C oncornaviruses are widespread among species of the animal kingdom and there are a number of reports implicating their presence in human beings. Several laboratories have reported evidence associating type-C oncornavirus with human malignancies by the presence of viral coat proteins, reverse transcriptase, and provirus DNA sequences (DNA copies of the viral RNA genome) in these tissues (7)(8)(9)(10)(11)(12)(13)(14). Isolations of type-C oncornaviruses from cultured human tissues have been reported (15)(16)(17)(18)(19), but are clearly uncommon (20).…”
mentioning
confidence: 99%
“…Various strains of type-C oncornaviruses are widespread among species of the animal kingdom and there are a number of reports implicating their presence in human beings. Several laboratories have reported evidence associating type-C oncornavirus with human malignancies by the presence of viral coat proteins, reverse transcriptase, and provirus DNA sequences (DNA copies of the viral RNA genome) in these tissues (7)(8)(9)(10)(11)(12)(13)(14). Isolations of type-C oncornaviruses from cultured human tissues have been reported (15)(16)(17)(18)(19), but are clearly uncommon (20).…”
mentioning
confidence: 99%
“…One recent study has indicated the lack of detectable reactivity of several human tissues tested in an immunoassay for interspecies determinants of p30 (34). The (18,19,35) are used, can lead to erroneous conclusions concerning the presence of type-C viral antigens.…”
mentioning
confidence: 99%
“…C-type particles have also been observed by electron microscopy in normal human placentas (8). Sherr and Todaro (9) have found antigens crossreacting with the p30 protein of baboon endogenous virus (BaEV) (10) and RD1 14 virus (11) in two human tumors, while Strand and August (12) have found similar reactivity in various normal and malignant human tissues. Antigenic crossreactivity to oncornavirus p30 protein has also been found in the kidney of a patient with lupus erythematosis (13), while material crossreacting with Mason Pfizer p30 protein has been detected in extracts of human breast cancer cells (14).…”
mentioning
confidence: 84%